Self and contextual perceptions in continuing entrepreneurs after a business interruption - Barrera Verdugo, Gustavo Alfonso. (Czestochowa University of Technology, 2021)
This research presents new evidence regarding perceptual differences among people who have and do not have recently interrupted a venture in Latin America. Particularly, it assesses discrepancies in self-perception, fear of failure, opportunity perception, and perceived ease of doing business. A comparative analysis between continuing and not continuing entrepreneurs, who are recently interrupted business in 11 Latin American countries, is performed through logistic regressions. The results support that continuing entrepreneurs tend to perceive fewer business opportunities and less facility to develop a new enterprise. Contrarily, they do not demonstrate significant differences in fear of failure. Instead, people who do not continue linked to ventures tend to show a higher fear of failure and a more upper grows up on positive self-perception. These findings contribute to design and improve programs that strengthen new ventures in people with interruption of business since, after this experience, no continuing entrepreneurs may be unemployed or left out the labour market and remained in poverty.
Osobiste i kontekstowe postrzeganie kontynuacji przedsiębiorcy po przerwanie w biznesie
Keywords: Business interruption.; Entrepreneur´s perceptions.; Continuing entrepreneurs.; Early-stage entrepreneurs.